Repower the Harbormaster Towers: Managing Maritime Artifacts in Java’s Port Cities - Aprilian, Rizki Dwika; Purbaya, Ricky; Alkadri, Miktha Farid (Blue Papers, 2026)
For centuries, Java played a pivotal role in the global shipping trade, connecting the spice islands with the Western world. Its northern coastline was home to three major port cities: Batavia (now Jakarta), Surabaya and Semarang, where trade was overseen by the syahbandar or harbormaster– a position dating from pre-colonial times. This role existed throughout the colonial era, when masonry towers with timber floors were constructed for harbormasters to manage port activities. Although revitalization efforts have emerged since the first decade of the twenty-first century, these towers have now been largely forgotten due to port relocations, land subsidence, sea-level rise and changes in ownership. Drawing on archival research and observation, this article examines how historic harbormaster towers in Java’s three major port cities are being preserved amid climate change challenges.
Keywords: heritage management; harbormaster; Syahbandar; Spice Route; Java